2007
DOI: 10.1002/art.22738
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic study of salivary peptides and proteins in patients with Sjögren's syndrome before and after pilocarpine treatment

Abstract: Objective. To investigate the effect of pilocarpine on the salivary peptide and protein profile in patients with primary Sjögren's syndrome (SS) and to study the differences between patients with primary SS, patients with SS associated with other rheumatic diseases, and healthy control subjects.Methods. Saliva specimens were obtained from 9 primary SS patients, 9 secondary SS patients, and 10 healthy controls. Samples were analyzed for levels of 62 different salivary proteins using high-performance liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 17 publications
(15 reference statements)
3
71
0
3
Order By: Relevance
“…Based on mass spectrometric screening, peptidome analysis is able to complete high throughout proteomic profiling within only a few hours [15,16], which could provide possible solutions of multiple biomarker detection for disease diagnosis. There are several studies performed essentially by analyzing saliva, tears, and salivary gland tissue in pSS [17][18][19][20][21][22]. Driss et al [23] identified a 7,606-Da biomarker peptide unique to the salivary samples from the SS subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Based on mass spectrometric screening, peptidome analysis is able to complete high throughout proteomic profiling within only a few hours [15,16], which could provide possible solutions of multiple biomarker detection for disease diagnosis. There are several studies performed essentially by analyzing saliva, tears, and salivary gland tissue in pSS [17][18][19][20][21][22]. Driss et al [23] identified a 7,606-Da biomarker peptide unique to the salivary samples from the SS subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Six studies have been performed in SS, and they are quite different in their principal goals as well as in their general methodologies (Ryu et al, 2006;Hu et al, 2007b;Peluso et al, 2007;Flesseig et al, 2009;Hu et al, 2011). Whole saliva or individual glands saliva have been examined, and samples were collected both in stimulated and unstimulated conditions.…”
Section: Salivamentioning
confidence: 99%
“…Peluso and colleagues (Peluso et al, 2007) analysed the differences in the salivary protein profiles of primary SS and secondary SS patients, and of control subjects using HPLC-ESI-MS. The authors collected whole saliva specimens from 9 primary SS patients, 9 secondary SS patients (3 Rheumatoid Arthritis-2° SS; 3 systemic sclerosis-2° SS; 3 systemic lupus erythematosus-2° SS), and 10 healthy controls, and they analysed the levels and frequencies of 62 proteins.…”
Section: Studymentioning
confidence: 99%
“…Therefore, changes to the saliva proteome provides information about the whole body and oral health: whole saliva contains proteins that can be informative for disease detection in oral health, [4][5][6][7][8][9][10][11] in particular for oral cancer, 12) head and neck squamous cell carcinoma 13) and Sjögren's syndrome. [14][15][16] Saliva, as a diagnostic fluid, has received a lot of attention recently, due to its relatively simple and non-invasive collection, 2) which is an important advantage, especially in sample collection from children and elderly people. In this review, we summarize current knowledge about the salivary proteome using mass spectrometry (MS) based technologies.…”
Section: Introductionmentioning
confidence: 99%